2017
DOI: 10.1186/s13012-017-0588-6
|View full text |Cite
|
Sign up to set email alerts
|

The association between implementation strategy use and the uptake of hepatitis C treatment in a national sample

Abstract: BackgroundHepatitis C virus (HCV) is a common and highly morbid illness. New medications that have much higher cure rates have become the new evidence-based practice in the field. Understanding the implementation of these new medications nationally provides an opportunity to advance the understanding of the role of implementation strategies in clinical outcomes on a large scale. The Expert Recommendations for Implementing Change (ERIC) study defined discrete implementation strategies and clustered these strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 67 publications
(104 citation statements)
references
References 19 publications
(17 reference statements)
3
93
0
Order By: Relevance
“…Contacts at 89 of 140 facilities completed the survey (64%) and reported using a median of 23 (IQR: 16-31) strategies. The median case review completion rate was 71% (IQR: 48%-95%).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Contacts at 89 of 140 facilities completed the survey (64%) and reported using a median of 23 (IQR: 16-31) strategies. The median case review completion rate was 71% (IQR: 48%-95%).…”
Section: Resultsmentioning
confidence: 99%
“…In both implementation efforts, early success was associated with training/education and tailoring to the context. 15,16 We also found that tailoring the survey for the STORM implementation effort allowed us to reduce the number of strategies that we assessed. The information that was learned from these assessments of stakeholder-reported implementation strategies in vastly different implementation efforts speaks to the value of this approach to assessing implementation strategies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations